Certificación de comercio justo en la competitividad del sector cacaotero ecuatoriano: un estudio comparativo entre productores certificados y no certificados. - Jara Cedillo, Edwin Patricio (Machala : Universidad Técnica de Machala, 2025)
Fair trade certification is a comprehensive process that seeks to ensure that products, such as cocoa, are produced and traded ethically and sustainably. This approach not only ensures fair prices for producers, but also promotes decent working conditions and responsible agricultural practices. In the context of the Ecuadorian cocoa sector, certification has allowed small producers to access differentiated markets, improve their well-being and contribute to the development of their communities. This research focuses on analyzing the effects of Fairtrade certification on the competitiveness of the cocoa sector, comparing certified and non-certified producers. The general objective of the research is to analyze the effects of Fairtrade certification on the competitiveness of the Ecuadorian cocoa sector. Specific objectives include assessing the impact of certification on cocoa sales prices, investigating its influence on access to international markets, analysing differences in cocoa quality between certified and non-certified producers, and examining the effect of certification on the social and economic development of producer communities. The research was carried out using a mixed approach, combining qualitative and quantitative methods. Data were collected from primary and secondary sources, including TradeMap and the Central Bank of Ecuador. Interviews were conducted with cocoa farmers in the province of El Oro, one certified and one non-certified, to obtain direct perspectives on the impact of certification. The research design was non-experimental and cross-sectional, allowing a snapshot of the current situation of the sector. The results revealed significant differences between certified and non-certified producers. Certified farmers experienced an increase in demand for their cocoa, access to higher prices, and the ability to reinvest in their communities. In addition, the certification allowed them to diversify their marketing channels and access international markets. In contrast, non-certified producers faced limitations in their competitiveness and access to markets, underscoring the importance of certification as a viable strategy to improve their economic situation. The SWOT analysis conducted in the research identified strengths such as access to fair prices and improvement in product quality, as well as opportunities in the growth of the sustainable products market. However, weaknesses were also pointed out, such as certification costs and lack of knowledge among non-certified producers, and threats such as global competition and fluctuations in consumer demand. Fair trade certification has proven to be a key driver for the social and economic development of cocoa-producing communities in Ecuador. By ensuring fair and stable prices, this certification not only improves the quality of life of farmers, but also allows them to invest in their communities. The creation of cooperatives and associations has strengthened social cohesion and promoted collaboration among producers, which contributes to the development of more resilient communities. However, it is critical to recognize the challenges associated with certification, such as costs and process complexity. To maximize benefits, it is recommended to implement training and awareness programs aimed at non-certified producers, encourage the creation of cooperatives and establish strategic alliances with organizations that promote fair trade. These actions will not only help level the playing field, but will also contribute to the sustainable development of the cocoa sector in Ecuador. In summary, Fairtrade certification has the potential to transform the sector, but its success depends on a collaborative approach and continued support to producers.
La certificación de comercio justo es un proceso integral que busca garantizar que los productos, como el cacao, se produzcan y comercialicen de manera ética y sostenible. Este enfoque no solo asegura precios justos para los productores, sino que también promueve condiciones laborales dignas y prácticas agrícolas responsables. En el contexto del sector cacaotero ecuatoriano, la certificación ha permitido a los pequeños productores acceder a mercados diferenciados, mejorar su bienestar y contribuir al desarrollo de sus comunidades. La presente investigación se centra en analizar los efectos de la certificación de comercio justo en la competitividad del sector cacaotero, comparando productores certificados y no certificados. El objetivo general de la investigación es analizar los efectos de la certificación de comercio justo en la competitividad del sector cacaotero ecuatoriano. Los objetivos específicos incluyen evaluar el impacto de la certificación en los precios de venta del cacao, investigar su influencia en el acceso a mercados internacionales, analizar las diferencias en la calidad del cacao entre productores certificados y no certificados, y examinar el efecto de la certificación en el desarrollo social y económico de las comunidades productoras. La investigación se llevó a cabo utilizando un enfoque mixto, combinando métodos cualitativos y cuantitativos. Se recopilaron datos de fuentes primarias y secundarias, incluyendo TradeMap y el Banco Central del Ecuador. Se realizaron entrevistas a productores de cacao en la provincia de El Oro, uno certificado y otro no certificado, para obtener perspectivas directas sobre el impacto de la certificación. El diseño de la investigación fue no experimental y transversal, permitiendo una instantánea de la situación actual del sector. Los resultados revelaron diferencias significativas entre los productores certificados y no certificados. Los productores certificados experimentaron un aumento en la demanda de su cacao, acceso a precios más altos y la capacidad de reinvertir en sus comunidades. Además, la certificación les permitió diversificar sus canales de comercialización y acceder a mercados internacionales. En contraste, los productores no certificados enfrentaron limitaciones en su competitividad y acceso a mercados, lo que subraya la importancia de la certificación como una estrategia viable para mejorar su situación económica. El análisis FODA realizado en la investigación identificó fortalezas como el acceso a precios justos y la mejora en la calidad del producto, así como oportunidades en el crecimiento del mercado de productos sostenibles. Sin embargo, también se señalaron debilidades, como los costos de certificación y la falta de conocimiento entre los productores no certificados, y amenazas como la competencia global y las fluctuaciones en la demanda del consumidor. La certificación de comercio justo ha demostrado ser un motor clave para el desarrollo social y económico de las comunidades productoras de cacao en Ecuador. Al garantizar precios justos y estables, esta certificación no solo mejora la calidad de vida de los agricultores, sino que también les permite invertir en sus comunidades. La creación de cooperativas y asociaciones ha fortalecido la cohesión social y promovido la colaboración entre los productores, lo que contribuye al desarrollo de comunidades más resilientes. No obstante, es fundamental reconocer los desafíos asociados con la certificación, como los costos y la complejidad del proceso. Para maximizar los beneficios, se recomienda implementar programas de capacitación y sensibilización dirigidos a productores no certificados, fomentar la creación de cooperativas y establecer alianzas estratégicas con organizaciones que promuevan el comercio justo. Estas acciones no solo ayudarán a nivelar el campo de juego, sino que también contribuirán al desarrollo sostenible del sector cacaotero en Ecuador. En resumen, la certificación de comercio justo tiene el potencial de transformar el sector, pero su éxito depende de un enfoque colaborativo y del apoyo continuo a los productores.
Keywords: COMERCIO JUSTO; COMPETITIVIDAD; PRODUCTIVIDAD; COMERCIALIZACIÓN